Utilizing Ice Cream Sticks as Simple Teaching Aids to Improve Elementary School Students' Ability to Count Objects Based on Geometric Shapes - Nurlailatun Ramdani; Nunung Fatimah; Fildzah Masturah (Abdi Masyarakat, 2026)
The ability to count objects based on geometric shapes is a fundamental aspect of early numeracy that should be developed from an early age. However, in lower primary classrooms, instruction is often delivered abstractly without the support of concrete media, making it difficult for students to grasp the concept. This community service activity aims to describe the implementation and impact of using ice cream sticks as simple instructional aids to improve the ability to count objects based on geometric shapes among first-grade elementary students. This study employed a qualitative descriptive method through observation, documentation, student work analysis, and informal interviews. The activity was conducted at SDN 16 Kota Bima, involving 20 first-grade students. The results show that using ice cream sticks helps students recognize geometric shapes, count concretely, engage actively, and strengthen mathematical representation and communication skills. These findings suggest that simple teaching aids can serve as effective, engaging, and contextual numeracy tools aligned with the principles of the Merdeka Curriculum